1994
DOI: 10.1002/1098-108x(199403)15:2<125::aid-eat2260150204>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of anorexia nervosa in males: 24 new cases

Abstract: As part of a larger prognostic study of anorexia nervosa, clinical features at presentation of 24 males with anorexia are described, and compared with a female group matched for date of admission. Data were extracted from the original case records and follow‐up interview. The study confirms the view that males display the classical syndrome of anorexia nervosa, but differs from previous studies in several respects. Age at onset (mean 18.6 years) and at presentation (mean 20.2 years) is later, with a mean durat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
65
4
5

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 34 publications
11
65
4
5
Order By: Relevance
“…W e rem ain, therefore, at the stage of focusing on individual case examples where a specific treatment approach has been adequately followed up. A controlled trial of treatment Ð that includes a significant proportion of m ale anorexics, who m ay be more prone to excessive exercising (Sharp et al, 1993); bulimics; and both restricting and bulimic anorexics Ð may help answer some of the questions posed. However, for the mom ent the findings of this study suggest that there are reasonable grounds for optimism in producing longterm change in the lives of patients with eating disorder.…”
Section: Discussionmentioning
confidence: 99%
“…W e rem ain, therefore, at the stage of focusing on individual case examples where a specific treatment approach has been adequately followed up. A controlled trial of treatment Ð that includes a significant proportion of m ale anorexics, who m ay be more prone to excessive exercising (Sharp et al, 1993); bulimics; and both restricting and bulimic anorexics Ð may help answer some of the questions posed. However, for the mom ent the findings of this study suggest that there are reasonable grounds for optimism in producing longterm change in the lives of patients with eating disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of premorbid obesity and overweight result to be more common in males than in females (Sharp et al, 1994;Fernández -Aranda et al, 2004), as well as a higher perfectionism and interpersonal distrust (Joiner et al, 2000). As Lewinsohn et al (2002) have indicated in their study, excessive exercising is more frequent in men than in women.…”
Section: Introductionmentioning
confidence: 89%
“…It has been suggested that individuals presenting with eating disorders originate from middle to upper social classes (Sharp et al, 1994). This social standing can be closely linked to the work that an individual does (Elias, 1997).…”
Section: Socio-economic Statusmentioning
confidence: 99%
“…Affective disorders, such as depression, appear to be the most commonly reported disorder (Anderson, 1999;Cariai et al, 1997;Olivardia et al, 1995;Sharp et al, 1994). Obsessional and anxiety disorders also appear to occur concurrently (Anderson, 1999;Garfinkel & Garner, 1982;Sharp et al 1994). Less common, but still apparent, are co-morbid substance abuse and personality disorders (Anderson, 2001;Cariât et al, 1997;Olivardia et al, 1995).…”
mentioning
confidence: 99%
See 1 more Smart Citation